2007
DOI: 10.7589/0090-3558-43.4.690
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Tadpole Mouthpart Depigmentation as a Diagnostic Test for Infection by Batrachochytrium Dendrobatidis for Four California Anurans

Abstract: ABSTRACT:The objective of this study was to evaluate the utility of gross morphologic examination of larval mouthpart defects as a diagnostic screening test to detect Batrachochytrium dendrobatidis infection in four California, USA, anuran species. We examined mouthparts of 2,034 tadpoles of Bufo boreas, Pseudacris regilla, and Rana catesbeiana collected in 2003 and 2004 and Bufo canorus collected in 2004. Data were recorded for three morphologic features: upper toothrows, lower toothrows, and combined jaw s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
(39 reference statements)
1
13
1
Order By: Relevance
“…Although some researchers have reported that mouthpart dekeratinization is not a good predictor of infection by Bd (Padgett-Flohr and Goble, 2007), our data from L. catesbeianus and H. cf. ornatus support findings of Fellers et al (2001), who reported that 67% of Rana muscosa tadpoles with missing or abnormally dekeratinized mouthparts were infected with Bd; Knapp and Morgan (2006), who reported that depigmentation of R. muscosa tadpole upper jaw sheaths was strongly associated with Bd infections (89%, 50 of 56) and Drake et al (2007), who reported that 70.3% of tadpoles from 5 frog and 3 toad species in southeastern United States had deformed jaw sheaths with dekeratinization the most common (50.3%) defect.…”
Section: Discussioncontrasting
confidence: 93%
“…Although some researchers have reported that mouthpart dekeratinization is not a good predictor of infection by Bd (Padgett-Flohr and Goble, 2007), our data from L. catesbeianus and H. cf. ornatus support findings of Fellers et al (2001), who reported that 67% of Rana muscosa tadpoles with missing or abnormally dekeratinized mouthparts were infected with Bd; Knapp and Morgan (2006), who reported that depigmentation of R. muscosa tadpole upper jaw sheaths was strongly associated with Bd infections (89%, 50 of 56) and Drake et al (2007), who reported that 70.3% of tadpoles from 5 frog and 3 toad species in southeastern United States had deformed jaw sheaths with dekeratinization the most common (50.3%) defect.…”
Section: Discussioncontrasting
confidence: 93%
“…Numerous environmental and developmental factors are capable of producing oral deformities in larval amphibians, and it would be erroneous to blindly use this phenomenon to diagnose chytridiomycosis (Altig 2007). For example, Padgett-Flohr & Goble (2007) found that for the 4 anuran species they tested, oral defects were not associated with B. dendrobatidis infection. Nonetheless, certain species such as those described herein do appear to show significant correlations between B. dendrobatidis infection and patterns of oral defects, again reiterating a phylogenetic link between B. dendrobatidis infection and pathological expression (Knapp & Morgan 2006, Drake et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Testing tadpoles with grossly abnormal mouthparts is a higher priority, as this may increase the chance of obtaining positive results (Fellers et al 2001, Rachowicz & Vredenburg 2004, Obendorf & Dalton 2006, Symonds et al 2007). However, the association between mouthpart abnormalities in tadpoles and infection with Bd may not occur in all species (Felger et al 2007, Padgett-Flohr & Goble 2007. In addition, abnormalities may occur for other reasons, such as low temperatures (Rachowicz & Vredenburg 2004).…”
Section: Key Aspects To Consider When Surveying Prioritiesmentioning
confidence: 99%